Revelation 1-5 - Aune, David E.; Nelson Electronic Publishing (Dallas, Texas : Word Books, Publisher, 1997)
.
System requirements: 486SX PC or better; 8MB RAM; Windows 3.1/95/98; DOS 3.3 or later; 15MB free hard drive space; 2X CD-ROM drive; sound card.
Keywords: Bible -- Commentaries; Bible. -- Versions. -- Revelation 1-5; Bible -- Dictionaries; Revelation 1-5 -- Commentaries